Research on cyberspace surveying and mapping technology - Fan ZHAO; Xiang-yang LUO; Fen-lin LIU (网络与信息安全学报)
Cyberspace surveying and mapping technology is a network common foundation and application technology.The research progress of cyberspace surveying and mapping technology was reviewed and discussed.Firstly,the con-notation and principle framework of cyberspace surveying and mapping technology was described.Secondly,relevant technologies were introduced in probing layer,mapping layer and drawing layer.Finally,some open problems in this field were discussed,and some interesting directions that may be worth researching in the future were indicated.